THE PHYTOCHEMICAL SCREENING HEXANE AND METHANOL EXTRACT OF SINYO NAKAL (DURANTA REPENS) - SUGITA, PURWANTININGSIH; AMILIA, RIZKI; ARIFIN, BUDI; RAHAYU, DYAH UTAMI CAHYANING; DIANHAR, HANHAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Phytochemicals are naturally present in every part of plants range from leaves, stem bark, and fruits to roots. The use of plant-based medicine is popular among individuals and communities in developing countries. This study evaluated that the phytochemical profile of Duranta repens fruits was collected from Jombang, East Java, Indonesia. Methods: Air-dried D. repens fruits were macerated by n-hexane and methanol, a separate flask. n-Hexane extract, then underwent saponification to remove fat. Then, the unsaponifiable of n-hexane and methanol extract was tested through phytochemical screening, respectively. Results: The methanol extract showed the presence of alkaloids, flavonoids, tannins, and steroids, but the unsaponifiable fraction only contained steroids. The unsaponifiable fraction was found to be a mixture of hydrocarbons ranging from C13-C20, fatty acids (palmitic and linoleic acid), squalene, and Vitamin E. Conclusion: The phytochemical screening of the plant plays an important role for pharmaceutical studies especially discovering new potential drugs for the treatment of various diseases.